Method for preparing spherical ethanol adsorption material for tail gas treatment through amplification at normal temperature and pressure
By using benzenequinone or aniline and NaOH to generate peroxy radical substances under normal temperature and pressure, the amplification preparation of MIL-100(Fe)@PAA-TEPA is achieved, which solves the problems of instability of MOFs particles and complex laboratory preparation processes, improves the ethanol adsorption performance and material stability, and promotes the development of the fuel ethanol industry.
Patent Information
- Application Number
- CN202510622486.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-15
AI Technical Summary
In the prior art, when preparing ethanol adsorption materials, the instability of MOFs particles leads to a decrease in adsorption performance, and the laboratory preparation process is complicated and energy consumption is high, making it difficult to achieve amplified preparation, which limits the development of the fuel ethanol industry.
Using organic amine graft-modified porous polyacrylate PAA-TEPA microspheres as carriers, MIL-100 (Fe) is grown by in situ crystallization under normal temperature and pressure, and using benzenequinone or aniline and NaOH to synergize peroxy radical substances to optimize the precursor solution, and amplification of the spherical composite MIL-100 (Fe)@PAA-TEPA, simplifying the operation steps and reducing costs.
It improves the ethanol adsorption performance, enhances the mechanical strength and stability of composite materials, reduces production costs, and promotes the treatment and industrial application of fuel ethanol fermentation exhaust gas.
Smart Images

Figure CN120479389A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of ethanol adsorption materials, in particular to a method for enlarging and preparing a spherical ethanol adsorption material for tail gas treatment under normal temperature and pressure conditions. Background Art
[0002] Under the current energy situation, it has become a top priority to develop green and renewable alternative energy sources to reduce dependence on fossil energy. Fuel ethanol, as a renewable clean energy source, is environmentally friendly and low-carbon, and has significant advantages in effectively alleviating the shortage of fossil fuels. The preparation of fuel ethanol is currently mainly achieved by biomass fermentation. However, the fermentation tail gas produced by the biomass fermentation process not only contains a large amount of carbon dioxide, but also contains atmospheric pollutants such as organic vapor, mainly ethanol. If these tail gases are not treated and are directly discharged into the atmosphere, it is very likely to cause secondary pollution and harm, and also cause waste of ethanol. Based on this, efficient, low-cost and low-energy tail gas treatment technology has vital application value in promoting the development of the fuel ethanol industry.
[0003] The adsorption method is used to treat ethanol fermentation tail gas with low energy consumption and high efficiency. The key lies in the adsorption material and adsorption-desorption process. Excellent adsorption materials and suitable adsorption-desorption processes will make the treatment of fermentation tail gas safer and more effective. Therefore, the research and development of adsorption materials is a hot spot in technological development. In recent years, people have developed ethanol adsorption materials prepared by loading MOFs particles on porous polymers. The physical adsorption of porous polymers is used to cooperate with the chemical adsorption between MOFs and ethanol to achieve a significant improvement in the ethanol adsorption performance. However, this composite material has shortcomings in preparation and use stability. On the one hand, since the MOFs particles in the composite material are mainly concentrated on the surface of the porous polymer material, they are unstable, causing the MOFs particles to easily fall off during multiple recycling processes, affecting the adsorption performance; on the other hand, the preparation of existing composite materials is mostly in the laboratory stage. The complexity of the process, the uniform dispersion of raw materials in the reaction process, and energy consumption and cost factors all bring difficulties to the scale-up preparation, limiting the industrial production and application of the adsorption material. Therefore, the development of a method suitable for the scale-up preparation of ethanol adsorption materials under normal temperature and pressure environments has a positive driving effect on improving the treatment effect of ethanol fermentation exhaust and promoting the large-scale development of fuel ethanol. Summary of the Invention
[0004] In response to the problems of difficulty in the scaled-up preparation of MOFs composite adsorption materials, complex preparation procedures, high energy consumption, and affected product structure and performance, the present invention has developed a method for the scaled-up preparation of spherical ethanol adsorption material MIL-100(Fe)@PAA-TEPA for exhaust gas treatment at room temperature and pressure. The method can stably prepare kilogram-level products, improve the microstructure of the spherical composite material, and enhance the adsorption performance for ethanol. Moreover, compared with laboratory preparation methods, the method reduces the amount of insoluble precursors, simplifies the operation steps, and shortens the reaction time, thereby significantly reducing production costs and improving the safety factor, providing technical support for the ultra-clean emission of ethanol in fuel ethanol fermentation exhaust gas.
[0005] To achieve the above objectives, the present invention provides a method for scaling up the preparation of spherical ethanol adsorption materials for exhaust gas treatment at room temperature and pressure. The method uses porous polyacrylate PAA-TEPA microspheres modified by grafting with organic amines as carriers. The PAA-TEPA microspheres are immersed in a MIL-100(Fe) precursor solution. MIL-100(Fe) is then in situ crystallized and grown on the inner surface of the PAA-TEPA microspheres under the action of peroxyl radicals at room temperature and pressure to obtain a spherical composite material MIL-100(Fe)@PAA-TEPA.
[0006] The preparation of PAA-TEPA microspheres and the in situ crystal growth of MIL-100(Fe) were both carried out using kilogram-scale scale-up preparation processes;
[0007] The in-situ crystallization growth of MIL-100(Fe) adopts a one-step impregnation method, which is to immerse PAA-TEPA microspheres in a MIL-100(Fe) precursor solution containing a metallic iron salt, an organic ligand, and a peroxyl radical-generating substance. The reaction is carried out at room temperature and pressure with a low stirring speed of 50-150 rpm / min to obtain MIL-100(Fe)@PAA-TEPA.
[0008] The peroxyl radical generating substance is a mixture of benzoquinone and NaOH, or a mixture of aniline and NaOH. The dosage ratio of the PAA-TEPA microspheres, the metal iron salt, the organic ligand, and the peroxyl radical generating substance is (330-1400 g): (1680-3110 g): (495-970 g): (30-75 g).
[0009] In view of the problems that exist in the laboratory process during the proportional scale-up preparation process, such as the impact on the loading rate and adsorption capacity of the composite material, the present invention changes the process of in-situ crystallization of MIL-100(Fe) of PAA-TEPA microspheres in the composite material, uses benzoquinone or aniline and sodium hydroxide as the peroxide radical generating substance, and jointly configures the MIL-100(Fe) precursor solution from a metal iron salt, an organic ligand and the peroxide radical generating substance. At the same time, the amount of the metal iron salt and the organic ligand in the precursor solution is reduced, the stirring speed of the in-situ crystallization process is controlled, and the impregnation treatment of the scale-up process is completed, thereby successfully realizing the scale-up preparation and optimization of the composite material. This not only simplifies the operating steps, reduces the production cost, shortens the reaction time, but also optimizes the quality of the adsorption material, providing technical support for the removal of ethanol in the exhaust gas of fuel ethanol fermentation.
[0010] Specifically, the benzoquinone or aniline in the precursor solution of the present invention and NaOH synergistically deprotonate the insoluble organic ligand H3BTC to generate BTC. 3- and with Fe 3+ The reaction generates peroxyl radicals (HOO·), which accelerate the reaction between iron ions and organic ligands at room temperature, enhance the coordination reaction rate, and thus promote the rapid formation of MIL-100(Fe) crystals, reduce the particle size of MIL-100(Fe) crystals, shorten the diffusion distance, and produce Zeolite-MTN topological structure. This three-dimensional network-like unique crystal pore structure is more conducive to the adsorption of ethanol, significantly improving the adsorption performance of the composite material. At the same time, the presence of benzoquinone or aniline enables the MIL-100(Fe) nanocrystals to be anchored uniformly and orderly inside the microsphere carrier under normal temperature and pressure conditions, which not only avoids the loss of adsorbed active substances, but also enhances the mechanical strength of the composite material, prolongs the service life of the composite material, and plays an important role in the in-situ crystallization growth of MIL-100(Fe) at room temperature and pressure. In addition, the amount of precursor used in the scale-up production is greatly reduced. For example, when ferric nitrate is used as the metal salt and trimesic acid is used as the organic ligand, MIL-100(Fe) can be grown in a uniform and orderly manner. PAA-TEPA :M 金属铁盐 :M 有机配体 The dosage ratio was adjusted from 5:101:30 in the laboratory process to 50:101:63. Based on the insolubility of the precursor, reducing the amount of precursor can greatly simplify the operation, and can also omit the drying step caused by step-by-step impregnation, thereby optimizing the scale-up preparation process.
[0011] As a limitation of the above technical solution, the organic ligand and the peroxyl radical generating substance are dissolved in N,N-dimethylformamide, the metal iron salt is dissolved in deionized water, and the two solutions are mixed to form a MIL-100 (Fe) precursor solution.
[0012] As a limitation of the above technical solution, the metal iron salt is selected from one or more of ferric nitrate, ferric chloride, ferric sulfate, and nano-iron oxide, and the organic ligand is selected from one or two of trimesic acid and terephthalic acid.
[0013] Improve the preparation of the precursor solution so that the metal iron salt, organic ligand and peroxyl radical generating substances can work synergistically to optimize the performance and use of the precursor solution.
[0014] As a limitation of the above technical solution, the preparation of porous polyacrylate PAA microspheres in PAA-TEPA microspheres is as follows: a polyacrylate monomer, a crosslinker, an emulsifier, a porogen and an initiator A are mixed as an oil phase, water is added to the oil phase, and stirred at a medium speed of 3000 to 5000 rpm / min, and a reducing agent A is added at the same time to obtain a stable emulsion; the emulsion is then slowly added to a dispersed phase containing water, initiator B, reducing agent B and a dispersant, and stirring is continued at a constant temperature of 55 to 75° C. for 0.5 to 1.0 hour to disperse the emulsion into uniform droplets, thereby completing polymerization and obtaining PAA microspheres;
[0015] The dosage ratio of each raw material is as follows: 20.0-30.0 wt.% of polyacrylate monomer, 20.0-30.0 wt.% of crosslinking agent, 2.0-3.5 wt.% of emulsifier, 38.0-43.0 wt.% of porogen, 2.0-2.5 wt.% of initiator A, 3.5-4.0 wt.% of reducing agent A in the emulsion. The sum of the percentages of each raw material except water in the emulsion is 100%. On the basis of keeping the other raw materials constant, the amount of polyacrylate monomer is adjusted to 100%; the amount of water added to the oil phase is 3.8-4.2 times the mass of the porogen; 98.0-98.5 wt.% of water, 0.1-1.0 wt.% of initiator B, and 3.5-4.0 wt.% of reducing agent B in the dispersed phase. 0.3-3.0 wt.%, dispersant 0.1-1.0 wt.%, the sum of the percentages of each raw material in the dispersed phase is 100%, and the amount of water is adjusted to 100% on the basis of fixing other raw materials.
[0016] As a limitation of the above technical solution, the polyacrylate monomer is at least one of glycidyl methacrylate, tert-butyl methacrylate, methyl acrylate, isobutyl acrylate, hydroxyethyl acrylate, and dimethylaminoethyl methacrylate;
[0017] The cross-linking agent is at least one of trimethylolpropane triacrylate, polyether polyisocyanate, and water-soluble carbodiimide;
[0018] The emulsifier is at least one of P-123 (PEG-PPG-PEG) and sodium dodecylbenzenesulfonate;
[0019] The porogen is at least one of toluene, cyclohexane, and polyvinyl pyrrolidone;
[0020] The initiator A is benzoyl peroxide or azobisisobutyronitrile;
[0021] The reducing agent A is N,N-dimethylaniline or ferrous ammonium sulfate;
[0022] The initiator B is ammonium persulfate or potassium persulfate;
[0023] The reducing agent B is N,N,N',N'-tetramethylethylenediamine or sodium sulfite;
[0024] The dispersant is polyvinyl alcohol or polyurethane block copolymer.
[0025] As a limitation of the above technical solution, the organic amine grafting modification of the porous polyacrylate PAA microspheres in the PAA-TEPA microspheres is to immerse the PAA microspheres in an organic amine solution and react at 100-130° C. for 12-24 hours; preferably, the mass ratio of the PAA microspheres and the organic amine solution is 1:(7-12).
[0026] As a limitation of the above technical solution, the organic amine solution is a mixed solution of methanol and tetraethylene pentamine. Preferably, the amount ratio of methanol to tetraethylene pentamine is 1:(5-6) by mass.
[0027] The present invention scales up the process for preparing porous polyacrylate (PAA) microspheres by adjusting the dosage ratio of each raw material. Specifically, the content of emulsifier (3.0-5.0 wt.%), porogen (40.0-45.0 wt.%), initiator A (1.0-1.5 wt.%), and reducing agent A (1.0-1.5 wt.%) in the oil phase of a laboratory process is adjusted to emulsifier (2.0-3.5 wt.%), porogen (38.0-43.0 wt.%), initiator A (2.0-2.5 wt.%), and reducing agent A (3.5-4.0 wt.%). The amount of water added to the oil phase is adjusted from 80-85 vol.% of the oil phase volume to 3.8-4.2 times the mass of the porogen. The dispersant in the dispersed phase is adjusted from 0.5-1.0 wt.% to 0.1-1.0 wt.%, so that the prepared porous polyacrylate (PAA) microspheres have a developed porosity and a unique tertiary pore structure. By grafting organic amines, the internal surface energy of the polyacrylate microspheres is significantly increased, resulting in local supersaturation of the MOF precursor on the microspheres' inner surfaces. This reduces the MOF crystallization nucleation energy barrier and provides suitable space and conditions for in-situ crystallization and uniform growth of MOFs on the microspheres' inner surfaces. Furthermore, the unique tertiary pore structure—interconnected channels between mesopores, micropores, and macropores—facilitates the full infiltration of metallic iron salts, organic ligands, and peroxyl radical-generating substances into the microspheres, promoting the rapid formation of MIL-100(Fe) crystals.
[0028] As a limitation of the above technical solution, the scaled-up preparation method includes the following process steps:
[0029] (1) Synthesis of PAA microspheres: 194-554 g of polyacrylate monomer, 189-540 g of cross-linking agent, 20-56 g of emulsifier, 300-860 g of porogen and 18-52 g of initiator A were mixed in a reactor as an oil phase. Subsequently, 1204-3440 mL of deionized water was added to the oil phase and stirred at 3000-6000 rpm. At the same time, 28-80 g of reducing agent A was added to obtain a stable emulsion. The emulsion was then slowly poured into a water bath heated stirring kettle containing a dispersed phase consisting of 5-10 L of deionized water, 14-40 g of initiator B, 74-150 g of reducing agent B and 10-20 g of dispersant. The mixture was stirred at a constant temperature of 55-75°C for 1 hour to disperse the emulsion into uniform droplets. After the polymerization was completed, the mixture was washed with clean water and dried to obtain 260-740 g of PAA microspheres.
[0030] (2) All the PAA microspheres prepared in step (1) were soaked in 2590-4440 g of an organic amine solution, reacted at 110° C. for 12 h, and the microspheres were taken out, washed with clean water, and dried to obtain 330-1400 g of PAA-TEPA microspheres;
[0031] (3) 495-970 g of the organic ligand and 30-75 g of the peroxyl radical generating substance are dissolved in 5000-7000 mL of N,N-dimethylformamide, and 1680-3110 g of the metal iron salt is dissolved in 6000-8000 mL of deionized water. The two solutions are mixed to form a MIL-100(Fe) precursor solution; all the PAA-TEPA microspheres prepared in step (2) are weighed and placed in a stainless steel reactor, and all the precursor solution is slowly added, and the reaction is continued at room temperature and pressure at a low speed of 50-150 rpm with slow stirring for 12-18 hours. After the reaction is completed, the product is washed with clean water and dried to obtain a spherical composite material MIL-100(Fe)@PAA-TEPA.
[0032] As a limitation of the above technical solution, the scaled-up preparation method includes the following process steps:
[0033] (1) Synthesis of PAA microspheres: 223.0±23g of glycidyl methacrylate, 54.0±6g of tert-butyl methacrylate, 269.0±27g of trimethylolpropane triacrylate, and P-123 28.0±3g, 430.0±43g of toluene and 26.0±3g of benzoyl peroxide were mixed in a 10L stainless steel reactor as the oil phase. Subsequently, 1720±172mL of deionized water was added to the oil phase and stirred at 4000±1000rpm / min. At the same time, 40±4g of N,N-dimethylaniline was added to obtain a stable emulsion; then the emulsion was slowly poured into a 20L water bath heated stirring tank containing 7±1L of deionized water, 19.6±2g of ammonium persulfate, 105±10g of N,N,N',N'-tetramethylethylenediamine and 14.0±1.4g of polyvinyl alcohol, and stirred at a constant temperature of 65℃ for 1h to disperse the emulsion into uniform droplets. After the polymerization was completed, it was washed with clean water and dried to obtain 370.0±40g of PAA microspheres.
[0034] (2) Take all the PAA microspheres prepared in step (1), soak them in a mixed solution of 700.0±70g methanol and 2810.0±280g tetraethylenepentamine, react at 110°C for 12h, take out the microspheres, wash them with clean water and dry them, and obtain 700.0±30g PAA-TEPA microspheres.
[0035] (3) Dissolve 882.0±44g of trimesic acid, 11.8±0.6g of aniline and 50±2.5g of sodium hydroxide in 6300mL of N,N-dimethylformamide, and dissolve 2828.0±140g of ferric nitrate nonahydrate in 7000mL of deionized water, and mix the two solutions to form a precursor solution; weigh all the PAA-TEPA microspheres prepared in step (2), put them into a 20L stainless steel reactor, slowly add the precursor solution, and continue to slowly stir at a low speed of 100±50rpm at room temperature and pressure for 12 to 18h. After the reaction is completed, wash the product with clean water and dry it to obtain 1261.0±30g of spherical composite material MIL-100(Fe)@PAA-TEPA.
[0036] As a limitation of the above technical solution, the 20L hydrothermal stirred reactor adopts a circulating water heating method.
[0037] To further optimize and improve the scale-up preparation method of composite materials, a 20L hydrothermal stirred reactor can be used to heat the emulsion suspension polymerization process with circulating water to ensure uniform reaction temperature, thereby avoiding the problem of uneven reaction rate due to inconsistent local temperature, which affects product performance.
[0038] In summary, the present invention solves the problems existing in the proportional scale-up process of laboratory preparation and forms a set of optimized scale-up processes, which can simplify the operating steps and shorten the reaction time, thereby significantly reducing production costs and improving the safety production coefficient. At the same time, it also optimizes the microstructure and adsorption properties of the composite material and enhances the mechanical strength of the composite material, thereby extending the service life. It provides a guarantee for the application of the composite material MIL-100(Fe)@PAA-TEPA in the treatment of fermentation tail gas and promotes the development of fuel ethanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 , (a) Electron microscope scanning image of the actual morphology of PAA-TEPA microspheres in Example 1; (b) Electron microscope scanning image of the surface pore structure of PAA-TEPA microspheres in Example 1; (c) and (d) Electron microscope scanning images of the internal structure of the MIL-100(Fe)@PAA-TEPA composite material in Example 1 at different magnifications.
[0040] Figure 2 , (a) Electron microscope scanning image of the true morphology of PAA-TEPA microspheres prepared by the laboratory process in Comparative Example 1; (b) Electron microscope scanning image of the surface pore structure of PAA-TEPA microspheres in Comparative Example 1; (c) and (d) Electron microscope scanning images of the internal structure of the MIL-100(Fe)@PAA-TEPA composite material in Comparative Example 1 at different magnifications.
[0041] Figure 3 , (a) and (b) SEM scanning images of the internal structure of comparative example 2 MIL-100(Fe)@PAA-TEPA composite material at different magnifications.
[0042] Figure 4 , Example 1 MIL-100(Fe)@PAA-TEPA composite material 20 adsorption and desorption cycle test data. DETAILED DESCRIPTION
[0043] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0044] The experimental methods in the following examples and comparative examples, unless otherwise specified, are conventional methods; the raw materials or test materials used, unless otherwise specified, are typical commercially available products. The quantitative tests in the following examples and comparative examples were all repeated three times, and the results were averaged.
[0045] Example 1
[0046] The kilogram-scale spherical ethanol adsorption material MIL-100(Fe)@PAA-TEPA was prepared at room temperature and pressure. The specific preparation operation is as follows.
[0047] (1) Synthesis of PAA microspheres: Glycidyl methacrylate (GMA, 223.0 g, 21.0 wt.%), tert-butyl methacrylate (TBMA, 54.0 g, 5.0 wt.%), trimethylolpropane triacrylate (TMPTA, 269.0 g, 25.1 wt.%), P-123 (28.0 g, 2.6 wt.%), toluene (430.0 g, 40.2 wt.%) and benzoyl peroxide (BPO, 26.0 g, 2.4 wt.%) were mixed in a 10 L stainless steel reactor as the oil phase. Subsequently, deionized water (1720 mL) was added to the oil phase and stirred at 4000 rpm / min for 7 minutes. During the stirring process, N,N-dimethylaniline (DMA, 40 g, 3.7 wt.%) was added to obtain a stable emulsion. The emulsion was then slowly poured into a 20 L water bath stirred tank containing a dispersed phase consisting of deionized water (7 L), ammonium persulfate (APS, 19.6 g, 0.27 wt.%), N,N,N',N'-tetramethylethylenediamine (TMEDA, 105 g, 1.47 wt.%) and polyvinyl alcohol (PVA, 14.0 g, 0.2 wt.%). The mixture was stirred continuously at a constant temperature of 65°C for 1 hour to ensure that the emulsion was dispersed into uniform droplets and complete the polymerization. The mixture was then washed with clean water and dried in a 60°C forced air drying oven to remove unreacted monomers and emulsifiers in the copolymer to obtain 370.0 g of spherical porous polyacrylate PAA microspheres.
[0048] (2) 370.0 g of PAA microspheres were immersed in a mixed solution of 700.0 g of methanol and 2810.0 g of tetraethylenepentamine (TEPA), reacted at 110 °C for 12 h, and the microspheres were taken out, washed with clean water, and dried to obtain 700.0 g of grafted PAA-TEPA microspheres.
[0049] (3) 882.0 g of trimesic acid (H3BTC), 11.8 g of aniline, and 50 g of sodium hydroxide were dissolved in 6300 mL of N,N-dimethylformamide (DMF), and 2828.0 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) was dissolved in 7000 mL of deionized water. The two solutions were mixed to form a precursor solution. 700.0 g of PAA-TEPA microspheres were placed in a 20 L stainless steel reactor, and the precursor solution was slowly added. The reaction was continued at room temperature and pressure at a speed of 100 rpm for 15 h. After the reaction was completed, the spherical product was removed, washed with clean water, and dried in a 60 ° C forced air drying oven to obtain 1261.0 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was recorded as composite material A.
[0050] The microstructure of PAA-TEPA microspheres and MIL-100(Fe)@PAA-TEPA microspheres was observed by scanning electron microscopy. Figure 1 .
[0051] The loading rate w of the spherical MIL-100(Fe)@PAA-TEPA composite material was calculated and its performance was tested. The calculation formula of the loading rate w is as follows:
[0052]
[0053] Where w is the loading rate (%), m1 is the mass of MIL-100(Fe)@PAA-TEPA composite material (g), and m2 is the mass of PAA-TEPA microspheres (g).
[0054] Calculation showed that the loading rate of composite material A was 44.5%. Using a BSD-VVS multi-station gravimetric gas vapor analyzer, the adsorption capacity was determined by weighing the weight change of the composite material before and after adsorption using the vacuum gravimetric method. The saturated ethanol adsorption capacity of composite material A at 35°C was measured to be 8.6 mmol / g.
[0055] Figure 1 In (a), the overall morphology of PAA-TEPA is observed to be a nearly perfect spherical particle with a diameter of approximately 1 mm. Its smooth surface and complete overall morphology make it suitable for use in fixed beds, fluidized beds, or separation columns. (b) is a magnified image of the surface of the PAA-TEPA microspheres, showing a relatively uniform distribution of pores, representing the pores left behind when toluene and water are removed. (c) and (d) clearly demonstrate the successful loading of MIL-100(Fe) into the PAA-TEPA microspheres.
[0056] Although Example 1 only lists one optimal raw material and dosage, based on the actual synthesis of the composite material, the dosage of each raw material can be adjusted within the optimal value range as described in the summary of the invention to meet the requirements.
[0057] Example 2
[0058] The same scaled-up preparation process for PAA-TEPA microspheres as in Example 1 was used to produce 700 g of microspheres. 970.0 g of HBTC, 12.5 g of aniline, and 53 g of sodium hydroxide were dissolved in 7000 mL of DMF. 3050 g of ferric chloride hexahydrate (FeCl3·6H2O) was dissolved in 6000 mL of deionized water. The two solutions were mixed to form a precursor solution. 700.0 g of PAA-TEPA microspheres were placed in a 20 L stainless steel reactor. The precursor solution was slowly added, and the mixture was stirred at 100 rpm for 15 h at room temperature and pressure. After the reaction, the spherical product was removed, washed with water, and dried in a forced-air drying oven at 60°C to obtain 1130.0 g of the spherical composite material MIL-100(Fe)@PAA-TEPA, designated Composite Material B.
[0059] The loading rate of spherical MIL-100(Fe)@PAA-TEPA composite materials was calculated and their performance was tested.
[0060] Calculation showed that the loading rate of composite material B was 38.1%. The adsorption capacity was determined by measuring the weight change of the composite material before and after adsorption using a BSD-VVS multi-station gravimetric gas vapor analyzer using the vacuum gravimetric method. The saturated ethanol adsorption capacity of composite material B at 35°C was found to be 6.9 mmol / g.
[0061] Example 3
[0062] The same scaled-up preparation process of PAA-TEPA microspheres as in Example 1 was used to obtain 700 g of microspheres. 550.0 g of H3BTC, 13.6 g of benzoquinone, and 50 g of sodium hydroxide were dissolved in 6300 mL of DMF, and 1800 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) was dissolved in 7000 mL of deionized water. The two solutions were mixed to form a precursor solution. The remaining steps and raw material amounts were kept consistent to obtain 1217 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was recorded as composite material C.
[0063] The loading rate of spherical MIL-100(Fe)@PAA-TEPA composite materials was calculated and their performance was tested.
[0064] Calculation shows that the loading rate of composite material C is 42.5%. The adsorption capacity was determined by measuring the weight change of the composite material before and after adsorption using a BSD-VVS multi-station gravimetric gas vapor analyzer using the vacuum gravimetric method. The saturated ethanol adsorption capacity of composite material C at 35°C was measured to be 8.2 mmol / g.
[0065] Example 4
[0066] (1) Synthesis of PAA microspheres: Glycidyl methacrylate (334.0 g, 17.4 wt.%), methyl acrylate (MA, 80.0 g, 4.2 wt.%), polyether polyisocyanate (PEI, 511.0 g, 26.6 wt.%), P-123 (53.2 g, 2.8 wt.%), toluene (817.0 g, 42.5 wt.%) and benzoyl peroxide (49.5 g, 2.5 wt.%) were mixed in a 10 L stainless steel reactor as the oil phase. Subsequently, deionized water (3268 mL) was added to the oil phase and stirred at 4000 rpm / min for 7 minutes. During the stirring process, N,N-dimethylaniline (76 mL, 4.0 wt.%) was added to obtain a stable emulsion; the emulsion was then slowly poured into a 20 L water bath heated stirring kettle containing deionized water (7 L), ammonium persulfate (19.6 g), N,N,N',N'-tetramethylethylenediamine (105 mL) and polyvinyl alcohol (14.0 g), and stirred continuously at a constant temperature of 65°C for 1 hour to ensure that the emulsion was dispersed into uniform droplets to complete the polymerization. The mixture was then washed with clean water and dried in a blast drying oven at 60°C to remove unreacted monomers and emulsifiers in the copolymer to obtain 365.0 g of spherical porous polyacrylate PAA microspheres.
[0067] (2) 365.0 g of PAA microspheres were immersed in a mixed solution of 700.0 g of methanol and 2810.0 g of tetraethylenepentamine (TEPA), reacted at 110 °C for 12 h, and the microspheres were taken out, washed with clean water and dried to obtain 688.0 g of grafted PAA-TEPA microspheres.
[0068] (3) 882.0 g of H3BTC, 11.8 g of aniline, and 50 g of sodium hydroxide were dissolved in 6300 mL of DMF, and 2828.0 g of Fe(NO3)3·9H2O was dissolved in 7000 mL of deionized water. The two solutions were mixed to form a precursor solution. 688.0 g of PAA-TEPA microspheres were placed in a 20 L stainless steel reactor. The precursor solution was slowly added and the mixture was stirred at 100 rpm for 15 h at room temperature and pressure. After the reaction, the spherical product was removed, washed with clean water, and dried in a forced air drying oven at 60°C to obtain 1235.0 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was designated as composite material D.
[0069] Calculation showed that the loading rate of composite material D was 44.3%. Using a BSD-VVS multi-station gravimetric gas vapor analyzer, the adsorption capacity was determined by weighing the weight change of the composite material before and after adsorption using the vacuum gravimetric method. The saturated ethanol adsorption capacity of composite material A at 35°C was measured to be 8.4 mmol / g.
[0070] Comparative Example 1
[0071] The ethanol adsorption material was prepared using a laboratory process. First, 0.2 g of PAA microspheres were prepared. Then, during in situ crystallization, benzoquinone and trimesic acid were added in the second impregnation process. The specific preparation operation is as follows.
[0072] (1) Synthesis of PAA: GMA 2.3 g (23.0 wt.%), TBMA 0.7 g (7.0 wt.%), TMPTA 2 g (20.0 wt.%), P-123 0.6 g (6.0 wt.%), toluene 3.9 g (39.0 wt.%), and BPO 0.2 g (2.0 wt.%) were mixed in a 25 mL beaker as the oil phase. Subsequently, 15 mL of deionized water was continuously added dropwise to the oil phase at 3000 rpm, and homogenized at 6000 rpm for 3 min. DMA (0.3 mL, 3.0 wt.%) was added during stirring, and homogenized at 8000 rpm for 2 min to obtain a stable emulsion. The emulsion was then slowly poured into a 250 mL three-necked flask containing 150 mL of deionized water, 0.24 g of APS, 0.4 mL of TMEDA, and 1.0 g of PVA. Stirring was continued at a constant temperature of 65°C for 30 min to ensure that the emulsion was dispersed into uniform droplets and complete the polymerization. The emulsion was then washed and dried with ethanol to remove unreacted monomers and emulsifiers in the copolymer to obtain spherical porous polyacrylate PAA microspheres.
[0073] (2) 0.2 g of PAA microspheres were soaked in a mixed solution of 2.0 g of methanol and 8.0 g of TEPA, and reacted at 110° C. for 12 h. The microspheres were taken out, washed with ethanol, and dried to obtain the grafted product PAA-TEPA microspheres.
[0074] (3) About 0.2 g of amine-grafted PAA-TEPA microspheres with macroporous structure were placed in a 25 ml flask, the flask was sealed with a double-valve constant pressure funnel and a bullhorn tube, and vacuum was applied at 343 K for 1 hour to keep the support beads in a vacuum state. At the same time, 4.04 g of Fe(NO3)·9H2O, 1.40 g of H3BTC and 21.6 mg of BQ were ultrasonically dissolved in 10 ml of DMF at 343 K to form a precursor solution. After the vacuum was completed, the heated precursor solution was poured into the flask and the vacuum operation was maintained. The reactants were allowed to fill the macropores of the polymer by impregnation. The dried spherical support was then poured into a flask containing 10 ml of deionized water together with the same weight of metal salt and organic ligand as in the precursor solution. The reaction was allowed to proceed at room temperature and pressure without stirring for 12 hours to prepare a room temperature MOF-polymer composite material. The spherical product was filtered using a 30 mesh sieve and washed 4 times with 30 ml of DMF after the reaction. It was then transferred to a vacuum oven and dried in vacuum at 423 K for 12 h to obtain 0.63 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was recorded as composite material E.
[0075] Calculation showed that the loading rate of the composite material E was 68.1%. The ethanol saturation adsorption capacity of the composite material E at 35° C. was measured by a BSD-VVS multi-station gravimetric gas vapor analyzer to be 13.8 mmol / g.
[0076] Figure 2 (a) shows the true morphology of the macroporous PAA-TEPA support, which is a regular sphere with a diameter of 1 mm. (b) shows the abundant micron-scale pores on the PAA-TEPA surface, which provide channels for the precursor solution to be impregnated. In (c) and (d), MIL-100(Fe) crystals are uniformly and orderly distributed on the PAA-TEPA support skeleton. This composite material retains the macroporous structure of PAA-TEPA while achieving nanoscale dispersion of MIL-100(Fe) crystals.
[0077] pass Figure 1 、 Figure 2 The microstructure comparison proves that the structure of the composite material prepared by scaled-up preparation is the same as that of the material prepared by laboratory process, indicating that the composite material has been successfully scaled up.
[0078] In addition, the laboratory process requires first impregnation with a precursor solution, followed by drying. The dried spherical carrier is then mixed with a mixed solution of metal salts, organic ligands, and water for room-temperature growth of the composite material. In the scaled-up preparation process of the present invention, the microspheres are directly crystallized and grown with the mixed precursor solution, eliminating the need for first impregnation, drying, and then changing the solution for crystallization growth, significantly simplifying the reaction steps. Furthermore, the present invention promotes the reaction through low-speed stirring during the crystallization growth process, changing the conventional static crystallization operation and making it more suitable for scaled-up preparation processes.
[0079] Comparative Example 2
[0080] The laboratory process of Comparative Example 1 was scaled up to prepare a spherical ethanol adsorption material. The specific preparation operation is as follows.
[0081] (1) Synthesis of PAA microspheres: GMA 250.0 g (23.1 wt.%), TBMA 76.0 g (7.0 wt.%), TMPTA 218.0 g (20.1 wt.%), P-123 60.0 g (5.5 wt.%), toluene 425.0 g (39.4 wt.%) and BPO 21.0 g (1.9 wt.%) were mixed in a 10 L stainless steel reactor as the oil phase. Subsequently, deionized water 1640 mL was added to the oil phase and stirred at 8000 rpm for 7 min. During the stirring process, DMA 33 mL (3.0 wt.%) was added to obtain a stable emulsion. The emulsion was then slowly poured into a 20L water bath stirred tank containing 7L of deionized water, 11.2g of APS, 18g of TMEDA, and 46.2g of PVA (during the scale-up experiment, it was found that more emulsion could be added to the dispersed phase while ensuring the performance of the composite material, thereby reducing the amount of dispersed phase used). Stirring was continued at a constant temperature of 65°C for 30min to ensure that the emulsion was dispersed into uniform droplets to complete the polymerization. The mixture was then washed with clean water and dried to remove unreacted monomers and emulsifiers in the copolymer to obtain 275.0g of spherical porous polyacrylate PAA microspheres.
[0082] (2) 275.0 g of PAA microspheres were immersed in a mixed solution of 522.0 g of methanol and 2090.0 g of TEPA, reacted at 110° C. for 12 h, and the microspheres were removed, washed with clean water, and dried to obtain 440 g of grafted PAA-TEPA microspheres.
[0083] (3) 440.0 g of PAA-TEPA microspheres were placed in a 20 L stainless steel reactor and vacuumed at 343 K for 1 hour to keep the support beads in a vacuum state. At the same time, 1600.0 g of Fe(NO3)·9H2O, 554.4 g of H3BTC and 8.6 g of BQ were ultrasonically dissolved in 3960 mL of DMF at 343 K to form a precursor solution. After the vacuum was completed, the heated precursor solution was poured into the flask and the vacuum operation was maintained. The reactants were allowed to fill the macropores of the polymer by impregnation. The dried spherical support and the same weight of metal salt and organic ligand as in the precursor solution were then poured into a flask containing 3960 mL of deionized water. The room temperature MOF-polymer composite material was prepared by reacting at room temperature and pressure without stirring for 12 hours. The spherical product was filtered using a 30 mesh sieve and washed 4 times with 1000 ml of DMF after the reaction. It was then transferred to a vacuum oven and dried in vacuum at 423 K for 12 h to obtain 582.0 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was recorded as composite material F.
[0084] Calculation showed that the loading rate was 24.4%. The ethanol saturation adsorption capacity of the composite material F at 35° C. was measured by a BSD-VVS multi-station gravimetric gas vapor analyzer to be 2.1 mmol / g.
[0085] The microstructure of the composite material prepared by scaling up is as follows: Figure 3 As shown, (a) and (b) are images of 500nm and 200nm inside the composite material, respectively. It can be seen from the figures that the crystal structure inside the microspheres is irregular and the loaded MIL-100(Fe) crystals are very few, resulting in insufficient adsorption performance of the material.
[0086] Comparative Example 3
[0087] 440.0 g of PAA-TEPA microspheres were obtained using the preparation process of Comparative Example 2, and then a composite material was prepared by increasing the amount of precursor.
[0088] 440.0 g of PAA-TEPA microspheres were placed in a 20-liter stainless steel reactor and vacuumed at 343 K for 1 hour to maintain the support spheres in a vacuum state. Simultaneously, 3100 g of Fe(NO3)·9H2O, 1074.0 g of H3BTC, and 16.7 g of BQ were dissolved in 7000 mL of DMF under ultrasonication at 343 K to form a precursor solution. After vacuuming, the heated precursor solution was poured into a flask and maintained under vacuum to allow the reactants to fill the macropores of the polymer through impregnation. The dried spherical support, along with the same weight of metal salt and organic ligand as used in the precursor solution, were then poured into a flask containing 7000 mL of deionized water. The reaction was continued at room temperature and pressure without stirring for 12 hours to prepare a room-temperature MOF-polymer composite. The spherical product was filtered through a 30-mesh sieve and washed four times with 1000 mL of DMF after the reaction. It was then transferred to a vacuum oven and dried in vacuum at 423 K for 12 h to obtain 610.0 g of spherical composite material MIL-100(Fe)@PAA-TEPA, which was recorded as composite material G.
[0089] Calculation showed that the loading rate was 27.8%. The ethanol saturation adsorption capacity of the composite material G at 35° C. was measured by a BSD-VVS multi-station gravimetric gas vapor analyzer to be 3.8 mmol / g.
[0090] Compared with Comparative Example 2, it can be seen that increasing the amount of precursor cannot effectively increase the loading rate of the composite material.
[0091] Comparative Example 4
[0092] Polyacrylate microspheres containing metal nanoparticles were prepared by adding a metal iron nanoparticle dispersion into an oil phase. The specific steps are as follows.
[0093] (1) Synthesis of PAA: GMA 223.0 g, TBMA 54.0 g, TMPTA 269.0 g, P-123 28.0 g, toluene 430.0 g, BPO 26.0 g, and 1680.0 g of nano-iron oxide dispersion (iron oxide content of 20 wt.%) were mixed in a 10 L stainless steel reactor as the oil phase. Subsequently, deionized water 1720 mL was added to the oil phase and stirred at 4000 rpm / min for 7 min. During the stirring, DMA 40 mL was added to obtain a stable emulsion. The emulsion was then slowly poured into a 10 L stainless steel reactor containing deionized water 7 L, APS 19.6 g, TMEDA 105 mL, and PVA. 14.0 g of the copolymer was placed in a 20 L water bath stirring kettle and stirred continuously at a constant temperature of 65 ° C for 1 h to ensure that the emulsion was dispersed into uniform droplets to complete the polymerization. It was then washed with clean water and dried to remove unreacted monomers and emulsifiers in the copolymer to obtain 534 g of spherical porous polyacrylate PAA (Fe) microspheres containing metal nanoparticles.
[0094] (2) 630.0 g of H3BTC and 9.72 g of BQ were dissolved in 4500 mL of DMF to form a precursor solution. 500.0 g of PAA(Fe) microspheres were placed in a 10 L stainless steel reactor and the precursor solution was slowly added. The reaction was incubated at room temperature and pressure for 12 h. After the reaction, the spherical product was removed, washed with water, and dried to obtain the spherical composite material MIL-100(Fe)@PAA, denoted as composite material H.
[0095] The loading rate was calculated to be 29.4%. The ethanol saturation adsorption capacity of the composite material H at 35° C. was measured by a BSD-VVS multi-station gravimetric gas vapor analyzer to be 4.1 mmol / g.
[0096] The loading rates of the composite materials of the examples and comparative examples and the results of the ethanol saturated adsorption capacity at 35° C. are summarized in Table 1.
[0097] Table 1
[0098]
[0099] Composite material E was prepared by the optimal laboratory process, and its loading rate and ethanol saturated adsorption capacity both reached the maximum.
[0100] Comparing composite materials A and E, although the loading rate of composite material A is lower due to the simplified scale-up process, reduced raw material usage and optimized cleaning method, and the ethanol saturation adsorption capacity is lower than that of composite material E due to the low loading rate, it is found through calculation that under the same loading conditions, composite material A reaches 95.4% of the saturation adsorption capacity of composite material E with the optimal process in the laboratory. This result is an optimal result for the scale-up process in practical applications and meets application requirements.
[0101] Comparison of composite materials B, C, and D shows that, in the scale-up process, replacing the iron source with FeCl3·6H2O, replacing the peroxyl radical-generating substance with a combination of benzoquinone and sodium hydroxide, or adjusting the raw material dosage of PAA-TEPA microspheres within a reasonable range can also produce composite materials with certain advantages, but none of them can achieve the performance of composite material A.
[0102] It can be seen from composite material F that the loading rate of the obtained composite material is greatly affected by the direct proportional scale-up preparation under laboratory process conditions, which is only 24.4%, and the saturated adsorption capacity of ethanol is only 2.1 mmol / g, which proves that it is not feasible to directly scale up the preparation by proportional scale-up of the laboratory process.
[0103] It can be seen from the composite material G that the adsorption performance of the composite material cannot be improved by simply increasing the amount of precursor. The loading rate is only 27.8%, and the saturated adsorption capacity of ethanol is only 3.8 mmol / g, which proves that it is not feasible to scale up the preparation by simply increasing the amount of precursor.
[0104] It can be seen from the composite material H that by directly adding metallic iron nanoparticles into the oil phase, first preparing polyacrylate microspheres containing nano-iron oxide, and then preparing the composite material at room temperature and normal pressure, the loading rate of the obtained composite material is also not ideal, only 29.4%, and its ethanol saturated adsorption capacity is 4.1 mmol / g, which is significantly lower than that of composite material A. It is difficult to meet application requirements with this performance.
[0105] In summary, the present invention is based on the laboratory preparation process of the composite material. By changing the in-situ crystallization MIL-100 (Fe) process of PAA-TEPA microspheres, aniline and sodium hydroxide are used as the substances for generating peroxyl radicals, while reducing the amount of metal iron salt and organic ligand in the precursor solution and controlling the stirring speed of the in-situ crystallization process, the scaled-up preparation of ethanol adsorption composite materials is successfully achieved, and the amount ratio of the raw materials used in the scaled-up preparation process is further adjusted to complete the optimization of the scaled-up preparation. The scaled-up preparation process formed simplifies the operation steps, shortens the reaction time, reduces the production cost, improves the safety production coefficient, and solves the problems existing in the laboratory preparation in the proportional scale-up process. At the same time, through Figure 4 It can be seen that after 20 cycle tests, the scaled-up composite material prepared by the present invention still maintains 95.4% of the initial adsorption performance. The composite material not only retains the microstructure and performance of the laboratory synthesized material, but also has a certain service life. This provides a guarantee for the application of the composite material MIL-100(Fe)@PAA-TEPA in the treatment of fermentation exhaust gas and provides technical support for the ultra-clean emission of ethanol in fuel ethanol fermentation exhaust gas.
[0106] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application. The description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of this application, several variations and improvements can be made, which all fall within the scope of protection of this application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure, characterized by: Using porous polyacrylate PAA-TEPA microspheres modified by organic amine grafting as carriers, the PAA-TEPA microspheres were immersed in a MIL-100(Fe) precursor solution. MIL-100(Fe) was then in situ crystallized and grown on the inner surface of the PAA-TEPA microspheres under the action of peroxyl radicals at room temperature and pressure to obtain spherical composite materials MIL-100(Fe)@PAA-TEPA. The preparation of PAA-TEPA microspheres and the in situ crystal growth of MIL-100(Fe) were both carried out using kilogram-scale scale-up preparation processes; The in-situ crystallization growth of MIL-100(Fe) adopts a one-step impregnation method, which is to immerse PAA-TEPA microspheres in a MIL-100(Fe) precursor solution containing a metallic iron salt, an organic ligand, and a peroxyl radical-generating substance. The reaction is carried out at room temperature and pressure with a low stirring speed of 50-150 rpm to obtain MIL-100(Fe)@PAA-TEPA. The peroxyl radical generating substance is a mixture of benzoquinone and NaOH, or a mixture of aniline and NaOH. The dosage ratio of the PAA-TEPA microspheres, the metal iron salt, the organic ligand, and the peroxyl radical generating substance is (330-1400 g): (1680-3110 g): (495-970 g): (30-75 g).
2. The method for amplifying the preparation of spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 1, characterized in that: The organic ligand and the peroxyl radical generating substance are dissolved in N,N-dimethylformamide, the metal iron salt is dissolved in deionized water, and the two solutions are mixed to form a MIL-100 (Fe) precursor solution.
3. The method for preparing a spherical ethanol adsorption material for tail gas treatment at room temperature and pressure according to claim 1, characterized in that: The metal iron salt is selected from one or more of ferric nitrate, ferric chloride, ferric sulfate, and nano-iron oxide, and the organic ligand is selected from one or two of trimesic acid and terephthalic acid.
4. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 1, characterized in that: The porous polyacrylate PAA microspheres in PAA-TEPA microspheres are prepared by mixing a polyacrylate monomer, a crosslinker, an emulsifier, a porogen, and an initiator A as an oil phase, adding water to the oil phase, stirring at a medium speed of 3000 to 5000 rpm, and simultaneously adding a reducing agent A to obtain a stable emulsion; then, the emulsion is slowly added to a dispersed phase containing water, an initiator B, a reducing agent B, and a dispersant, and stirring is continued at a constant temperature of 55 to 75° C. for 0.5 to 1.5 hours to disperse the emulsion into uniform droplets, thereby completing polymerization and obtaining PAA microspheres; The dosage ratio of each raw material is as follows: 20.0-30.0 wt.% of polyacrylate monomer, 20.0-30.0 wt.% of crosslinking agent, 2.0-3.5 wt.% of emulsifier, 38.0-43.0 wt.% of porogen, 2.0-2.5 wt.% of initiator A, and 3.5-4.0 wt.% of reducing agent A in the emulsion; the amount of water added to the oil phase is 3.8-4.2 times the mass of the porogen; 98.0-98.5 wt.% of water, 0.1-1.0 wt.% of initiator B, 0.3-3.0 wt.% of reducing agent B, and 0.1-1.0 wt.% of dispersant in the dispersed phase.
5. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 4, characterized in that: The polyacrylate monomer is at least one of glycidyl methacrylate, tert-butyl methacrylate, methyl acrylate, isobutyl acrylate, hydroxyethyl acrylate, and dimethylaminoethyl methacrylate; The cross-linking agent is at least one of trimethylolpropane triacrylate, polyether polyisocyanate, and water-soluble carbodiimide; The emulsifier is at least one of P-123 and sodium dodecylbenzene sulfonate; The porogen is at least one of toluene, cyclohexane, and polyvinyl pyrrolidone; The initiator A is benzoyl peroxide or azobisisobutyronitrile; The reducing agent A is N,N-dimethylaniline or ferrous ammonium sulfate; The initiator B is ammonium persulfate or potassium persulfate; The reducing agent B is N,N,N',N'-tetramethylethylenediamine or sodium sulfite; The dispersant is polyvinyl alcohol or polyurethane block copolymer.
6. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 1, characterized in that: The organic amine grafting modification of porous polyacrylate PAA microspheres in PAA-TEPA microspheres is carried out by immersing the PAA microspheres in an organic amine solution and reacting them at 100-130° C. for 12-24 hours.
7. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 6, characterized in that: The organic amine solution is a mixed solution of methanol and tetraethylenepentamine.
8. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to any one of claims 1 to 7, characterized in that: The scaled-up preparation method includes the following process steps: (1) Synthesis of PAA microspheres: 194-554 g of polyacrylate monomer, 189-540 g of crosslinking agent, 20-56 g of emulsifier, 300-860 g of porogen and 18-52 g of initiator A were mixed in a reactor as an oil phase. Subsequently, 1204-3440 mL of deionized water was added to the oil phase and stirred at a medium speed of 3000-6000 rpm. At the same time, 28-80 g of reducing agent A was added to obtain a stable emulsion. The emulsion was then slowly poured into a water bath heated stirring kettle containing a dispersed phase consisting of 5-10 L of deionized water, 14-40 g of initiator B, 74-150 g of reducing agent B and 10-20 g of dispersant. The mixture was stirred at a constant temperature of 55-75° C. for 1 hour to disperse the emulsion into uniform droplets. After the polymerization was completed, the mixture was washed with clean water and dried to obtain 260-740 g of PAA microspheres. (2) All the PAA microspheres prepared in step (1) were soaked in 2590-4440 g of an organic amine solution, reacted at 110° C. for 12 h, and the microspheres were taken out, washed with clean water, and dried to obtain 330-1400 g of PAA-TEPA microspheres; (3) Dissolve 495-970 g of the organic ligand and 30-75 g of the peroxyl radical generating substance in 5000-7000 mL of N,N-dimethylformamide, and dissolve 1680-3110 g of the metal iron salt in 6000-8000 mL of deionized water. Mix the two solutions to form a MIL-100(Fe) precursor solution. Take all the PAA-TEPA microspheres prepared in step (2), put them into a stainless steel reactor, slowly add all the precursor solutions, and continue to stir slowly at a low speed of 50-150 rpm at room temperature and pressure for 12-18 hours. After the reaction is completed, wash the product with clean water and dry it to obtain a spherical composite material MIL-100(Fe)@PAA-TEPA.
9. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 8, characterized in that: The scaled-up preparation method includes the following process steps: (1) Synthesis of PAA microspheres: 223.0±23g of glycidyl methacrylate, 54.0±6g of tert-butyl methacrylate, 269.0±27g of trimethylolpropane triacrylate, and P-123 28.0±3g, 430.0±43g of toluene and 26.0±3g of benzoyl peroxide were mixed in a 10L stainless steel reactor as the oil phase. Subsequently, 1720±172mL of deionized water was added to the oil phase and stirred at 4000±1000rpm. At the same time, 40±4g of N,N-dimethylaniline was added to obtain a stable emulsion; then the emulsion was slowly poured into a 20L water bath heated stirring tank containing 7±1L of deionized water, 19.6±2g of ammonium persulfate, 105±10g of N,N,N',N'-tetramethylethylenediamine and 14.0±1.4g of polyvinyl alcohol, and stirred at a constant temperature of 65°C for 1h to disperse the emulsion into uniform droplets. After the polymerization was completed, it was washed with clean water and dried to obtain 370.0±40g of PAA microspheres. (2) Take all the PAA microspheres prepared in step (1), soak them in a mixed solution of 700.0±70g methanol and 2810.0±280g tetraethylenepentamine, react at 110°C for 12h, take out the microspheres, wash them with clean water and dry them to obtain 700.0±30g PAA-TEPA microspheres. (3) 882.0±44g of trimesic acid, 11.8±0.6g of aniline and 50±2.5g of sodium hydroxide were dissolved in 6300mL of N,N-dimethylformamide, and 2828.0±140g of ferric nitrate nonahydrate was dissolved in 7000mL of deionized water. The two solutions were mixed to form a precursor solution; all the PAA-TEPA microspheres prepared in step (2) were taken and placed in a 20L stainless steel reactor, the precursor solution was slowly added, and the reaction was continued at a low speed of 100±50rpm with slow stirring for 12 to 18h at room temperature and pressure. After the reaction was completed, the product was washed with clean water and dried to obtain 1261.0±30g of spherical composite material MIL-100(Fe)@PAA-TEPA.
10. The method for preparing spherical ethanol adsorption materials for tail gas treatment at room temperature and pressure according to claim 9, characterized in that: The 20L water bath heating stirred tank adopts circulating water heating method.
